Decolorization Of Indigosol Blue Dye Using Trametes versicolor F200 and Aspergillus sp - Pertiwi, Sunu; Dewi, Ratna Stia; Sari, Ajeng Arum (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
The dyeing process of batik eventually produces much of wastewater. The difficult degradation and the dangers posed within the synthetic dyes are the main concerns in finding efficient wastewater treatment. Biological treatment has been known to be an effective technique of reducing or eliminating color intensity in wastewater. Fungi is one organism that can decompose many environmental pollutants. The aims of this research were to determine the ability of fungal isolates in decolorizing the synthetic dyes and analyzed which treatment has the highest decolorization percentage. Fungal isolates of Trametes versicolor F200 and Aspergillus sp. were used as a biological agent to decolorize of Indigosol Blue dye. The decolorization percentage was analyzed by spectrophotometer method. The result showed that T. versicolor F200 and Aspergillus sp. able to decolorize Indigosol Blue dye. The decolorization treatment of Indigosol Blue dyes using T. versicolor F200 showed the highest decolorization percentage reaching 97.21%.